Techno-economic analysis of tandem photovoltaic systems - Peters, I. M.; Sofia, S.; Mailoa, J.; Buonassisi, T. (RSC Advances, 2016)
Tandem solar cells offer the potential of conversion efficiencies exceeding those of single-junction solar cells, but also incur higher fabrication costs. The question arises under which conditions a tandem solar cell becomes economically preferable to both of the single-junction sub-cells it comprises. We present an analysis based on cost and efficiency relations to answer this question for a double-junction tandem solar cell. We find that combining two ideally band-gap-matched single-junction solar cell technologies into a tandem should be a "marriage of equals": the sub cells should be produced at similar per W costs, both sub cells should have similar efficiencies when operated independently, and the costs to turn both cells into a system should be similar. We discuss examples of different hypothetical and actual tandem solar cell technologies and show the intricacies of imbalances in the mentioned factors. We find that tandem-solar-cell-based PV power stations for existing solar-cell technologies offer the potential to reduce the levelized cost of electricity (LCOE), provided suitable top cells are developed.
CRIS-Team Scopus Importer:2023-03-07